ADHD in context: Young adults' reports of the impact of occupational environment on the manifestation of ADHD. (July 2016) - Lasky, Arielle K.; Weisner, Thomas S.; Jensen, Peter S.; Hinshaw, Stephen P.; Hechtman, Lily; Arnold, L. Eugene; W. Murray, Desiree; Swanson, James M.
Abstract: Does changing context play a role in the decline in ADHD symptoms in adulthood? Insufficient research has explored the functioning of adults with ADHD. As adults, individuals with ADHD have significantly more latitude to control aspects of their day-to-day environments. Do the new contexts young adults find themselves in alter their experience of ADHD? Are there particular occupational or educational contexts in which young adults report functioning better than others? To examine this issue, we conducted semi-structured interviews at four North American sites in 2010–11 with 125 young adults, originally diagnosed with ADHD as children, regarding their work and post-secondary educational environments. Many subjects describe their symptoms as context-dependent. In some contexts, participants report feeling better able to focus; in others, their symptoms—such as high energy levels—become strengths rather than liabilities. Modal descriptions included tasks that were stressful and challenging, novel and required multitasking, busy and fast-paced, physically demanding or hands-on, and/or intrinsically interesting. Consistent with a developmental psychopathology framework, ADHD is experienced as arising from an interaction between our subjects and their environments. These findings demonstrate the need to account for the role of context in our understanding of ADHD as a psychiatric disorder, especially as it manifests in young adulthood. Highlights: Explores the influence of work on young adults' ADHD symptoms through interviews. Subjects view ADHD symptoms as context-dependent, improving in stimulating jobs. Subjects desired highly-stimulating work environments. Subjects experience ADHD as an interaction between themselves and their environment. Context is important in our understanding and treatment of ADHD.